Automated deduction – CADE 26 : 26th International Conference on Automated Deduction, Gothenburg, Sweden, August 6-11, 2017, Proceedings /: 26th International Conference on Automated Deduction, Gothenburg, Sweden, August 6-11, 2017, Proceedings. (2017) - Unknown
No abstract available